Basic requirements and principles of creation onboard diagnostic systems of locomotives - Bodnar, YE. B. (Science and Transport Progress, 2014)
Purpose. Justification of the basic principles of construction on-board diagnostic systems locomotive and choose from high-performance and reliable interface for the exchange of information on-board diagnostic systems. Methodology. Problem of getting correct and adequate information about the technical state of the technical object is solved with the use and compliance of the fundamental principles of modern computers. Findings. High-performance and reliable interface to exchange messages between different units of management systems and on-board diagnostic systems was selected. Properties which are required high data rate, high reliability and low error rate of information transfer. Originality. The main principles of building on-board diagnostic systems which ensure compliance locomotives accumulation of accurate and adequate information about the technical condition which is necessary to organize its maintenance and repair were formulated. Practical value. Diagnostic equipment designed with use of requirements set forth above and principles will affect the technical condition of the engine, increasing the likelihood of uptime, productivity and locomotive repair teams. The introduction of on-board diagnostic systems and stationary locomotives will significantly improve the system and optimize their maintenance costs of maintenance and repairs. Besides, information about diagnostic parameters changing accumulated with the aim of airborne systems will be used in order to create mathematical models that, in turn, will organize a system of maintenance and predict the technical condition of locomotives.